Putting power in perspective: a systematic review of power dynamics in social-ecological traps - Miles Lambert-Peck; Pierre Echaubard; Osamu Saito; Maiko Nishi (Discover Sustainability)
Abstract This paper explores the use of power and politics in empirical literature on social-ecological traps. Social-ecological traps describe conditions where self-reinforcing interactions between social and ecological elements perpetuate a system in an unfavorable or undesirable state. Researchers across disciplines have theorized the nature and composition of social-ecological traps. In this connection, critical viewpoints on resilience have recognized a growing need to investigate political context, power relations, and the unequal distribution of risks and benefits contributing to the capacity of communities to manage changing conditions. However, it remains unclear to what extent empirical studies support any theorized way of power and politics influencing trap dynamics. This paper reviews power dynamics in the existing literature and offers insight into how power influences the emergence and persistence of social-ecological traps. Through a systematic literature review, we examined how the concept of power has been used, explicitly and implicitly, in empirical social-ecological trap research. The review identified 40 publications, focusing mainly on coastal ecosystems and cultivated areas within Latin America, Sub-Saharan Africa, and Asia. Our results suggest that power is still poorly understood from both a conceptual and operational perspective within the social-ecological trap literature. A few studies that do center power in their analyses demonstrate that despite limited attention, there are clear instances where power intersects with social-ecological system dynamics to perpetuate resilient, yet undesirable outcomes. We point to the absence of empirical studies that systematically analyze power relationships and dynamics and highlight the need for further research that bridges socio-political and ecological analyses.